Eksplorasi Karya Sastra Mengenai Nilai-Nilai Edukatif Melalui Analisis Novel “Laskar Pelangi” Karya Andrea Hirata - Salsabillah Syahriza; Zahratul Ummami; Syahrul Ramadhan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to explore literary works regarding the educational values ​​in the novel "Laskar Pelangi". The method used is a qualitative approach, which uses descriptive methods and observational analysis. The results of this research show the existence of various educational values ​​such as the value of education, the value of hard work and perseverance, friendship and solidarity, and optimism and hope. Analyzing the values ​​in “Laskar Pelangi” helps us to improve the quality and credibility of our knowledge.